O cardume - Coelho, Tiago Pinto (2015)
Imagination and creativity as indispensable tools in the built of visual languages that rediscover and strengthen the way of seeing and being in the world. A methodology that is committed to create relations as stimulus, promoting the use and consolidation of creative thinking as an indispensable tool to the growth of each individual in an embracing and exploratory way towards reality